INFLUENCE OF ORGANIC AND INORGANIC SOURCES OF NUTRIENTS ON FORAGE PRODUCTIVITY AND ECONOMICS OF OAT (AVENA SATIVA L.) - Kumar, SUNIL; DHAR, SHIVA (Annals of Agricultural Research, 2014)
A field experiement was conducted at Indian Grassland and Fodder Research Institute during Rabi seasons of 1996-97 to 1998-99 to access the productivity and economics of forage oat with the combined use of organic and inorganic sources of nutrients. The treatments comprised of vermicompost 10 t/ha, FYM 10 t/ha, 100% recommended dose of NPK (80:40:0), vermicompost 5 /ha, FYM 5 t/ha, 50% recommended dose of NPK + vermicompost 5 t/ha, 50% recommended dose of NPK + FYM 5 t/ha, 50% recommended dose of NPK (40:20:0) + vermicrompost 5 t/ha + FYM 5 t/ha gave significantly higher green fodder, dry matter and crude protein yields of oat than the other treatments. The forage yield exhibited superiority with the treatments where growth parameters attained maximum values. However, the results of forage and crude protein yield were comparable with 100% recommended dose of NPK. Highest net return (Rs. 11575/ha) and benefit: cost ratio (2.60) was obtained with 100% recommended dose of NPK and was significantly higher than best treatment with regard to forage and crude protein yields i.e. 50% recommended dose of NPK + vermincompost 5 t/ha + FYM 5 t/ha (1.14).